Architectural drawing : a visual compendium of types and methods - Yee, Rendow, 1942- (New Jersey : John Wiley & Sons, 2013)
A comprehensive compendium of architectural drawing types and methods, both hand drawn and computer generated. Yee has updated this edition to reflect the growing influence of digital drawing.
Companion web site [Bonus chapters] : Conventional and computerized representation in color -- Interfacing manual and digital media: Case studies of architects Antoine Predock and Zaha Hadid -- Interfacing manual and digital media: academic studio examples -- Appendix : Geometric forms in architecture ; Geometric definitions ; Descriptive geometric principles ; Measuring point system ; Shadows and sun's rays vanishing points.
Includes bibliographical references (pages 567-568) and indexes.
Architecture
Keywords: Architectural drawing -- Technique; Architecture and Planning; Architectural drawing -- Technique; Architectural drawing -- Technique; Architectural structure & design; Architecture; Architecture: professional practice; Architecture and Planning